Sputtering Deposition of Ultra-thin α-Fe2O3 Films for Solar Water Splitting. Issue 6 (June 2015) - Jia, Lichao; Harbauer, Karsten; Bogdanoff, Peter; Ellmer, Kluas; Fiechter, Sebastian
Abstract : Ultra-thin α-Fe2 O3 (hematite) films have been deposited by radio frequency (RF) sputtering technique and photoelectrochemically investigated towards their ability to oxidize water. By varying the deposition power and time as well as the sputter gas flow (argon), the microstructure and morphology of the film were optimized. It was found that the increment in the film thickness resulted in the loss of efficiency for solar water oxidation. The film with a thickness of 27 nm exhibited the best result with a maximum photocurrent of 0.25 mA cm −2 at 1.23 VRHE . Addition of small amounts of O2 to the sputter gas improved the photoactivity significantly.